1997
DOI: 10.1074/jbc.272.14.9153
|View full text |Cite
|
Sign up to set email alerts
|

Control of Activity through Oxidative Modification at the Conserved Residue Cys66 of Aryl Sulfotransferase IV

Abstract: Oxidation at Cys66 of rat liver aryl suflotransferase IV alters the enzyme's catalytic activity, pH optima and substrate specificity. Although this is a cytosolic detoxification enzyme, the pH optimum for the standard assay substrate 4-nitrophenol is at pH 5.5; upon oxidation, the optimum changes to the physiological pH range. The principal effect of the change in pH optimum is activation, which is manifest by an increase in K'cat without any major influence on substrate binding. In contrast, with tyrosine met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
65
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(72 citation statements)
references
References 27 publications
(24 reference statements)
7
65
0
Order By: Relevance
“…Incubation of enzyme with 1 mM GSSG or 1 mM DTNB, however, resulted in a slight but distinct increase in activity. Observations of such changes in activity as the result of formation of mixed disulfides with glutathione have been made (13-16) and, in one instance, were found, due to the formation of a disulfide bond between two protein cysteine residues (16).…”
Section: Resultsmentioning
confidence: 99%
“…Incubation of enzyme with 1 mM GSSG or 1 mM DTNB, however, resulted in a slight but distinct increase in activity. Observations of such changes in activity as the result of formation of mixed disulfides with glutathione have been made (13-16) and, in one instance, were found, due to the formation of a disulfide bond between two protein cysteine residues (16).…”
Section: Resultsmentioning
confidence: 99%
“…R ecently, substrate specificity investigations along with specificity constant (k cat /K M ) measurements have provided significant insights into a number of biologically important enzymes [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Specificity studies of an enzyme for different natural or synthetic substrates can help determine the enzyme structure and physiological functions [1, 4 -7] as well as address the key residues involved in substrate binding and catalysis [2,8].…”
mentioning
confidence: 99%
“…The novobiocic acid noviosyl transferase activity of NovM and its specificity for various substrate analogs in designing novel coumarinbased antibiotics was recently characterized by Walsh and coworkers [3]. In addition, efforts have been made to alter enzymes by site-directed mutagenesis in order to manipulate substrate specificity [12][13][14] or enhance enzyme catalysis [15].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One of the more intriguing aspects of the mechanism of rSULT1A1 is the sensitivity of the enzyme to changes in its redox environment (Marshall et al, 2000). Studies with homogeneous preparations of the enzyme have indicated that treatment with thiol oxidants such as diamide and GSSG results in increases in the specific activity of rSULT1A1 with 4-nitrophenol as substrate (Marshall et al, 1997(Marshall et al, , 1998(Marshall et al, , 2000. In studies with GSSG as the oxidant, these effects were clearly shown to be attributable to sequential oxidation of cysteine residues in rSULT1A1, with initial formation of an S-glutathionylated protein involving cysteine 66, followed by formation of an intramolecular protein disulfide between cysteines 66 and 232 (Marshall et al, 1997(Marshall et al, , 2000.…”
Section: Introductionmentioning
confidence: 99%